Examination of the Coping Flexibility Hypothesis Using the Coping Flexibility Scale-Revised - Kato, Tsukasa (Frontiers in Psychology, 2020)
Coping flexibility, as defined by the dual-process theory, refers to one’s ability to relinquish a coping strategy recognized as ineffective—abandonment—and to devise and implement an alternative and more effective strategy—re-coping. The coping flexibility hypothesis (CFH) dictates that richer coping flexibility produces more adaptive outcomes caused by stress response, such as reduced psychological and physical dysfunction. We tested the reliability and validity of the Coping Flexibility Scale-Revised (CFS-R) and the CFH using the CFS-R, which was developed to measure coping flexibility. In total, we performed three studies involving 6,752 participants. Study 1 provided the psychometric properties of the CFS-R and tested this factorial structure by a confirmatory factor analysis. Study 2 estimated the validity of the CFS-R by examining the associations between its three subscales and variables that were conceptually similar to them. Study 3 tested the CFH using a longitudinal design after controlling for the effects of typical coping strategies and other types of coping flexibility. Overall, the CFH was supported by the use of the CFS-R, and the findings in Studies 2 and 3 showed that it had acceptable validity and reliability. Our findings implied that abandonment and re-coping can predict reduced depressive symptoms more than other types of theoretical framings for coping flexibility. Additionally, a meta-analysis of the Cronbach’s alphas for all samples in this study (k = 9, N = 6,752) showed that they were 0.87 (95% CI [0.87, 0.88]) for abandonment, 0.92 (95% CI [0.91, 0.92]) for re-coping, and 0.86 (95% CI [0.85, 0.87]) for meta-coping.